Research Map on Islamic Audit Literatures - Mimma Maripatul Uula (Review on Islamic Accounting, 2022)
This study aims to see the development of research "Islamic Auditâ€ around the world published by journals with that theme. This study used a qualitative method with a blibliometric analysis approach. The data used is secondary data with the theme "Islamic Auditâ€ which comes from the Scopus database. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the research development blibliometric map "Islamic Audit". Based on the bibliometric keyword mapping, there are 6 clusters that can be research lines. The 6 clusters are (1) Shariah audit governance, (2) Development of Islamic audit control, (3) Shariah compliance for Islamic audit, (4) Corporate governance in Islamic auditing, (5) Audit report lag and extent in Islamic auditing, and (6) Risk management in Islamic audit. Then the words most used are shariah audit, effectiveness, system, Islamic financial institution, governance, and shariah compliance.